2012
DOI: 10.1016/j.bpobgyn.2012.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Malignant ovarian germ-cell tumours

Abstract: Malignant ovarian germ-cell tumours account for about 5% of all ovarian malignancies and typically present in the teenage years. They are almost always unilateral and are exquisitely chemosensitive. As such, the surgical approach in young women with such tumours confined to a single ovary should aim to preserve fertility. In early disease, a unilateral salpingo-oophorectomy with careful surgical staging is of great importance in selecting appropriate adjuvant therapy. In advanced disease, the role of aggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 70 publications
4
67
1
8
Order By: Relevance
“…However, we found one case age 50 years that presented with stage IIIA, mixed type consisted of EST and immature teratoma. MOGCT in the fifth decade is quite rare (Low et al, 2012). Solheim et al (Solheim et al, 2013) reviewed 351 Norwegian patients with MOGCT and found that patients over 50 years old had a significantly poorer prognosis than younger patients consistent with this case in our study that showed an uneventful outcome even though she received many chemotherapy regimens.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…However, we found one case age 50 years that presented with stage IIIA, mixed type consisted of EST and immature teratoma. MOGCT in the fifth decade is quite rare (Low et al, 2012). Solheim et al (Solheim et al, 2013) reviewed 351 Norwegian patients with MOGCT and found that patients over 50 years old had a significantly poorer prognosis than younger patients consistent with this case in our study that showed an uneventful outcome even though she received many chemotherapy regimens.…”
Section: Discussionsupporting
confidence: 74%
“…Although, dysgerminoma represented the most common type of MOGCT in the literature review (Bhurgri et al, 2011., Low et al, 2012, we found dysgerminoa was the third ranking histology in our study while the first ranking was immature teratoma and the second ranking was EST. This finding resembled the Weinberg et al publication (Weinberg et al, 2011).…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…Dysgerminomas on the other hand constitute a group of slower growing tumors, which can present with nonspecific abdominal symptoms. Less common signs include abdominal distension, fever, ascites and vaginal bleeding [1,3,42,43]. Staging is according to the FIGO system, as for epithelial ovarian cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian germ cell tumors (OGCTs) are rare, comprising 2% to 5% of all ovarian malignancies [1]. OGCTs usually occur in young women, with a peak incidence at age 20 years and rare reports when age is over 40 years [2].…”
Section: Introductionmentioning
confidence: 99%